To Improve the Students’ Writing Skill on Narrative Text Through of the Animation Movies of Junior High School - Jontra Jusat Pangaribuan; Meikardo Samuel Prayuda (Universitas Muhammadiyah Mataram, 2021)
This research aims to improve whether Animation movie media can improve the student's writing skills and to know the students’ responses after being taught by using Animation movie media. This research is Classroom Action Research (CAR) which was conducted by applying Animation movie media to the students of SMP GKPI Pamen Medan. As the collaborator, the English teacher and the writer collaboratively discussed the result of the study. They concluded that the use of animation movies could be an effective way to help students in writing. It was shown in histogram 4.4, in which the mean score of each test improved. The mean score of the pre-test was 50,37, the formative test was 67,22, and the post-test was 79,25. Those scores showed that the second cycle was better than the first cycle. Besides that, the improvement could be seen from the observation sheet, field notes, and questionnaire. Most of the students were more active and enthusiastic during the process of teaching and learning from the first to second cycle when the media was applied. The percentage of students responses in questionnaire, the students responses in strongly agree is 60(3,75%), agree 79(49,37%), quite agree 18(11,25%), disagree 3(18,75%). The score showed that the student's responses were good and also animation movie media can improve their writing skill in narrative text. In conclusion, animation movie is suitable media to improve students’ writing skill because this media gave students a chance more active. As the result, the student's writing score test increased in both cycles after being taught with animation movies and also had a good response toward the learning-teaching process through the application of animation movies.